Permainan Tradisional Terhadap Minat Belajar Siswa dalam Aktivitas Pembelajaran Pendidikan Jasmani Sytematic Literature Review - Muhammad, Khansa; Rahmat, Alit; Carsiwan, Carsiwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effectiveness of traditional games in increasing students' interest in learning in physical education learning activities at school. The method used in this research uses the SLR (Systematic Literature Review) method, literature searches are carried out using digital databases (Scopus, Science Direct, and Google Scholar). By searching using the keywords Traditional Games, Physical Education, and Interest in Learning. The research results show that traditional games have a very significant influence on students' interest in learning in physical education learning activities at school. Conclusion, that applying traditional games is an interesting and fun approach to improving children's physical fitness and psychomotor skills, and student participation in physical education classes, and can improve students' physical education learning activities at school. Keywords: Interest in Learning, Physical Education, Traditional Games